Plato's Cleitophon: On Socrates and the Modern Mind - Kremer, Mark (Lexington Books, 2004)
It had been thought that theCleitophon was a spurious dialogue. Its brevity and the fact that Socrates does not respond to accusations from Cleitophon suggested to scholars that it was only a fragment. However, in the last fifteen years, the complete and authentic dialogue was rediscovered. Upon its discovery, scholars have almost universally agreed that the Cleitophon is the introduction to Plato'sRepublic. In Plato's Cleitophon: On Socrates and the Modern Mind editor, translator, and author, Mark Kremer, has mined some of the best scholarship on the relationship of Plato's Cleitophon and its relationship to modern thought. It is the contention of the editor that the Cleitophon, is an ancient example of the psychic, social, cultural, and moral strain that is put upon the citizens of a republic when their society begins to erode on all fronts. This work has the potential to afford readers an ancient perspective on ourselves by showing us how we appear in Plato's mind. It should be read by anyone who has ever read Plato'sRepublic; as well as anyone who is concerned about the social, psychic, cultural, and moral effects of postmodernity and globalization.